Analisis Penyebab Terjadinya Missfile Berkas Rekam Medis di Ruangan Filling RS St Elisabeth Batam Kota - Riza Suci Ernaman Putri; Retno Kusumo; Yuni Utami (Yayasan Literasi Sains Indonesia, 2022)
This research is motivated by the occurrence of missfiles in terms of searching for medical record files where officers who borrow medical record documents do not write in the expedition book which causes obstacles in carrying out patient actions. The officer is not careful in preparing the medical record file where the document will be used but it is not on the proper shelf The study was to determine the flow of medical record file retrieval, to find out the flow of medical record file storage and the causes of missfiles in the medical record file filling room at St Elisabeth Hospital Batam City. This study uses a qualitative method. The data collection of this research was carried out by the researcher by means of interviews and observations. The population of this study consisted of four medical record officers and 1 nurse. Result: when the service is seen from the Man and Method factors, including the man factor, namely the level of education and work experience of officers. The method factor is that 100% of SOPs have not been implemented on returning and borrowing medical record files because there are still officers who do not know the correct application of SOPs. This is what causes the missfile in the filling room. Conclusion: The officers did not focus when filling out the medical record files due to the fatigue of the officers, the lack of thoroughness of the officers and the rush of the officers when they wanted to fill in the medical record files which could cause missfiles and where the return and loan SOPs did not work.